Determination of antimycotic and antioxidant activities in Morus nigra L (black mulberry) leaves extract grown in Malaysia / Shafinaz Mohammad Yusuf - Mohammad Yusuf, Shafinaz (2015)
Spreading of Candidiasis cause by Candida albicans required more effective treatment that is not harmful to the patient. The presence of antioxidant properties could be a treatment for debilitating disease from free radical that contains with high reactive compound, which contributes to damage many structures of cell in human body. Morus nigra L (black mulberry) native from China is popular as the traditional herb due to the medicinal properties and phytochemical composition. The present study was designed to observe the antimycotic properties against Candida albicans (ATCC 60193) and antioxidant activity of Morus nigra L leaves extract grown in Malaysia. Antimycotic effect of Morus nigra L leaves extract was evaluated by Minimimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC) and Antimycotic Sensitivity Testing (AST). For antioxidant activities evaluation, the DPPH radical scavenging assay was carried out. The methanol extract of Morus nigra L leaves extract was found to be active against Candida albicans and it was determined to have antioxidant activities. The Minimum Inhibitory Concentration (MIC) determined to be 37.5mg/ml and Minimum Fungicidal Concentration (MFC) for methanol extract of Morus nigra L leaves were determined to be 75.5mg/ml while the Antimycotic Sensitivity Testing showed effects of the inhibition zone on PDA media for concentration 1000mg/ml, 500mg/ml, 250mg/ml and 75.5mg/m. Besides, the results of comparison between Morus nigra L and L-ascorbic acid in antioxidant activity proved that there are significantly (p<0.05). It revealed that methanolic extract of the Morus nigra L leaves contain potential antioxidant activity.